The hospitalization burden of all-cause pneumonia in China: a population-based study, 2009–2017 - Hu, Y; Han, Y; Yu, C; Guo, Y; Pei, P; Yang, L; Chen, Y; Du, H; Sun, D; Pang, Y; Niu, W; Burgess, S; et al. (Elsevier, 2022)
Background Pneumonia represents a public health problem of substantial health and economic burden. However, the evidence on the burden of adult pneumonia is limited in China.